Innovations at Ukrainian enterprises: use of information and communication technologies - S. Babych; D. Babych (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Економіка)
Innovative direction of the country's development contributes to its economic growth. Innovations are considered to be an important factor for achieving success in competi-tive and global economy. The use of innovations can improve the level of communica-tion between market stakeholders. The correct implementation of innovations and the use of innovative potential by enterprises helps to increase their competitiveness and achieve success in the market. Thus, assessing the current state and determining the prospects for the implementation of innovative activities at enterprises is an actual is-sue. The aim of the study is to analyze the indicators of innovations implementation in terms of the use of information and communication technologies (ICT) at Ukrainian enterprises. The main indicators characterizing the activities of business entities in Ukraine during 2018–2022 are considered, in particular, their number and volumes of products (goods, services) sold. A downward trend in the values of the indicators is revealed, which is due, in particular, to the COVID-19 pandemic and the full-scale war in Ukraine. The directions of use of information and communication technologies are determined, namely: access to the Internet, use of social media, cloud computing ser-vices. The dynamics of the number of enterprises connected to the Internet is character-ized by fluctuations and a sharp decline in 2022. Social networks are the most popular way of using social media among Ukrainian enterprises. Social networks provide an opportunity to create a community between market participants. In addition, it is one of the advertising channels, an opportunity to attract the target audience and establish long-term relationships with the consumer for success in the market. Only about 10% of all enterprises in Ukraine use cloud computing services. The article presents a subjective assessment, namely, the results of a survey of Ukraini-an companies based on 2023 data regarding using the new technologies, including: ChatGPT and Artificial Intelligence, cloud services and data storage, online services and platforms for remote work organization, QES for personal identification, CRM sys-tems for working with clients, creation of mobile applications and chatbots in messen-gers. In addition, in 2023, Ukrainian companies, using their innovative potential, have implemented an upgrade of work processes and have chosen directions for strategic changes in difficult operating conditions.